1979
DOI: 10.2134/agronj1979.00021962007100010026x
|View full text |Cite
|
Sign up to set email alerts
|

No‐Tillage Maize Production in Chemically Suppressed Grass Sod1

Abstract: For no‐tillage maize (Zea mays L.) planted in sod, production usually involves the use of a contact herbicide to chemically mow or kill the grass sod. Such a procedure often necessitates costly forage reestablishment and subjects the land to water and wind erosion hazards during noncrop periods. Substantial acreage of rolling, erosive land presently is being row cropped. Field studies on different soil types were designed to investigate: a) the feasibility of chemically suppressing the grass sod for maize prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
34
0

Year Published

1982
1982
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 4 publications
3
34
0
Order By: Relevance
“…The maize grain yield reduction for LM treatment maize is similar to other reports in that excessive competition from LM resulted in lower grain yield than conventional maize (Adams et al, 1970;Carreker et al, 1972;Robertson et al, 1976;Flynn et al, 2013). Grasses in our study had rapid post-suppression recovery and expanded into the strip-tilled maize rows, exceeding the 60% cover or effective chemical suppression that other reports have found integral to support maize yield in LM systems (Elkins et al, 1979(Elkins et al, , 1983. Previous reports attribute observed yield suppression of maize in LM to early-season stresses (Flynn et al, 2013;Bartel et al, 2017).…”
Section: Maize Total Aboveground Biomass Stover Yield Grain Yield supporting
confidence: 87%
See 2 more Smart Citations
“…The maize grain yield reduction for LM treatment maize is similar to other reports in that excessive competition from LM resulted in lower grain yield than conventional maize (Adams et al, 1970;Carreker et al, 1972;Robertson et al, 1976;Flynn et al, 2013). Grasses in our study had rapid post-suppression recovery and expanded into the strip-tilled maize rows, exceeding the 60% cover or effective chemical suppression that other reports have found integral to support maize yield in LM systems (Elkins et al, 1979(Elkins et al, , 1983. Previous reports attribute observed yield suppression of maize in LM to early-season stresses (Flynn et al, 2013;Bartel et al, 2017).…”
Section: Maize Total Aboveground Biomass Stover Yield Grain Yield supporting
confidence: 87%
“…Similar maize grain yield observed under a variety of tillage methods was attributed to LM species compatibility (Beale and Langdale, 1964). Effective chemical suppression in conjunction with cool-season species dormancy facilitates an advantage for maize in LM in the competition for resources (Elkins et al, 1979). The inadequately suppressed LM in our experiment likely functioned as an early-season weed, which can initiate the shade avoidance responses in maize during the critical period for weed control regardless of resources abundance (Page et al, 2009).…”
Section: Maize Total Aboveground Biomass Stover Yield Grain Yield mentioning
confidence: 80%
See 1 more Smart Citation
“…Difficulty in forage stand termination is a major reason why many producers keep alfalfa stands longer than required for maximum rotational benefits (Entz et al 1995). Adams et al (1970), Carreker et al (1972), Elkins et al (1979), and Smith et al (1992a) all stressed a need for no-till cropping systems to replace conventional methods of removing perennial sod. There is increasing interest among producers in the Canadian Prairies and northern US Great Plains in using herbicides instead of traditional tillage methods to suppress alfalfa stands (Entz et al 1995;Anderson and Halvorson 1996).…”
mentioning
confidence: 99%
“…For example, without suppression, a white clover living mulch reduced the yield of sweet corn (Nicholson and Wien, 1983;Vrabel, 1981Vrabel, , 1983Peters, 1986) and cabbage (Nicholson and Wien, 1983;Wyland, 1986). On the other hand, the use of intercropped forages in corn production has generally been successful when the sods were chemically suppressed (Adams et al, 1970;Bennett et al, 1976;Box et al, 1980;Elkins et al, 1979;Hartwig, 1974). In New York, Vrabel (1981,1983) showed that sweet corn intercropped with white clover suppressed by atrazine (6-chloro-N-ethyl-N'-(lmethylethyl)-l,3,5-triazine-2,4-diamine) yielded as well or better than clean cultivated corn, depending on the year.…”
Section: Introductionmentioning
confidence: 99%